Social Media and Strategic Leadership - Kyprianou, Christina (Edward Elgar Publishing, 2024)
This chapter discusses both the benefits and risks of social media for strategic leaders, and develops a framework of leader social media engagement through a strategic lens. It first identifies key individual, organizational, and environmental attributes influencing the goals leaders may pursue through social media. It subsequently considers the impact of these goals on five social media engagement choices, and theorizes the impact of these choices on cognitive, affective, and relational strategic processes. The resulting framework aims to inspire future research at the intersection of social media and strategic leadership, as well as equip practitioners with a deeper understanding of the potential drivers and outcomes of their social media activity.
Keywords: Social media; Leadership; Stakeholder engagement; Strategy; Management; Decision making; 53 Ciencias Económicas; ODS 12 - Producción y consumo responsables; ODS 16 - Paz, justicia e instituciones sólidas